PERTOBATAN EKOLOGIS DALAM TERANG ENSIKLIK LAUDATO SI - Maru, Titus Paulus Maru; Silan, Kristofel; Lengkey, Seravin (Department of Theology - Sekolah Tinggi Filsafat Seminari Pineleng, 2024)
The focus of this scientific paper is ecological conversion. The author sees it from the perspective of Pope Francis Laudato Si's Encyclical. Today it cannot be hidden that injustice to the environment, flora and fauna, natural resources, and fellow human beings is a serious problem. The author can call this problem ecological injustice. Because of that, the author takes the theme of ecological repentance in the light of the Encyclical Laudato Si. The purpose of this scientific writing is that the writer discover the concept of ecological conversion and realizes the concept of ecological conversion in the light of Laudato Si's Encyclical. In the process of scientific writing, the author uses two sources. The first source, let's say as a primary source, is the Encyclical Laudato Si. The second source as a secondary source is an article that has been previously written by another author. The author searches for these sources by using Google. The trick is to search for Google Scholar. The author uses the method of reading and analyzing primary sources and secondary sources as a reference to further strengthen the author's argument. After about 1 month, the writer managed to find two points as the purpose of this writing. First, the concept of repentance according to Laudato Si, realizes that the earth belongs together as brothers and sisters. This requires confessing sin as a form of God's presence in the world. What is prioritized is the motivation born of spirituality to preserve nature. Second, realizing the concept of ecological repentance. we must have education and spirituality as capital to view other creations as brothers. This from the Encyclical Laudato Si is proof that the Catholic Church has a living love, so that love is manifested with a sense of concern for God's fellow creatures.